Characterisation of pectins extracted from different parts of Malaysian durian rinds - Jong, Sze Hui; Abdullah, Norazlin; Muhammad, Norhayati (2021)
Durian rinds are a potential source of pectin. The rinds consist of the outer layer of the fruit which is semiwoody and thorny and the inner layer, which is creamy white. Pectin may be present in varying amounts in different parts of the rind. Previous studies only investigated pectin content from the inner part of the rinds. Therefore, it is essential to provide scientific data on the pectin yield from whole durian rinds (including the thorns). Particularly, this information can be useful when preparing durian rinds for pectin extraction.